The Influence of The Whatsapp Application On Students' Ability to Write Procudure Texts - Huda, Rahmat; Lestari, Nida (Jurnal Hata Poda, 2024)
The problem formulation in this research is "What is the influence of using WhatsApp in writing procedural texts before and after in class VII MTs Panca Dharma Padang Sidempuan?" Class VII students at MTs Panca Dharma Padang Sidempuan. 2) To determine students' ability to write Procedure Text after using WhatsApp for class VII students at MTs Panca Dharma Padang Sidempuan. In this research the author uses associative research.  Associative research is an attempt to explain and find a description of the two variables, as well as see the influence between the two variables. Based on the results of research carried out by the author using a formula and the calculated value obtained from using the WhatsApp group is = 76, while the calculation without using the WhatsApp group is = 48 with a sample size of 15. Based on the calculation above, the author has found that the results using WhatsApp are greater than without using WhatsApp. Thus, that is = 76 48. From this score, the hypothesis is accepted.